Mathematics and statistics for the quantitative sciences - Betti, Matthew (Applied mathematician) (Boca Raton : C&H/CRC Press, 2023)
"Mathematics and Statistics for the Quantitative Sciences was born from a radical reimagining of first-year mathematics. While calculus is often seen as the foundational mathematics required for any scientist, this often leads to mathematics being seen as some, ultimately useless, hoop that needs to be jumped through in order to do what someone really wants to do. This sentiment is everywhere at every level of education. It even shows up in how people stereotype mathematics courses. What this book aims to do, therefore, is serve as a foundational text in everyday mathematics in a way that is both engaging and practically useful. The book seeks to teach the mathematics needed to start to answer fundamental questions like 'why' or 'how'. Why do we only need to take census data once every few years? How do we determine the optimal dosing of a new pharmaceutical without killing people in the process? Or, more generally, what does it even mean to be average? Or what does it mean for two things to actually be different? These questions require a different way of thinking - a quantitative intuition that goes beyond rote memorization and equips readers to meet the quantitative challenges inherent in any applied discipline. Features Draws from a diverse range of fields to make the applications as inclusive as possible Would be ideal as a foundational mathematical and statistical textbook for any applied quantitative science course"--
Includes bibliographical references and index.
Keywords: Mathematics